PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS LECTORA INSPIRE PADA POKOK BAHASAN LAJU REAKSI DI SMA/MA - Oktavianti, Nur Azlina; Linda, Roza; ', Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research about development of learning based on Lectora Inspire media has been done. Learning media that developed is Lectora Inspire with using Research Development of modification Four - D model, include stages Define, Design and Development by eliminating Disseminate stage. Data collect technique by validating Lectora Inpire to three validators (media expert and matter experts) and given average score of assessment is 95.63 %. Assessment for practically media test using trial of practitioners (users), there are three teachers and 15 students from class XI. Data analysis of learning media based on questionnaire responses of teachers and students each earned an average score of 96.67 % and 97.3 %. Average score overall validation and trial practitioners of learning media based on Lectora Inspire show that this media is valid and can be use in learning process.Keywords : Learning Media, Lectora Inspire, Rate of Reaction